Mechanics and electrodynamics of magneto-and electro-elastic materials - Ogden, R. W. 1943-; Steigmann, David J.; SpringerLink (Online service). (Wien New York Springer, 2011)
This volume presents a state-of-the-art overview of the continuum theory of both electro- and magneto-sensitive elastomers and polymers, which includes mathematical and computational apsects of the modelling of these materials from the point of view of material properties and, in particular, the "smart-material" control of their mechanical properties.
PREFACE; Table of Contents; Electromagnetics in Deformable Solids; 1 Introduction; 1.1 Basic Aspects: Maxwell, Heaviside, Lorentz: Physics versus Electrical Engineering; Modeling Nonlinear Electroelastic Materials; 1 Introduction; Magnetostatics: from Basic Principles to Nonlinear Interactions in Deformable Media; 1 Introduction; Analysis of Nonlinear Electrostatic Membranes; 1 Introduction; Computational Nonlinear Electro-Elasticity -- Getting Started -; 1 Introduction; Electro-Mechanical Response of Nematic Elastomers: an Introduction; 1 Introduction
Includes bibliographical references
Electronic reproduction.
Keywords: Continuum mechanics; Smart materials; Membranes (Technology); Electromagnetism